Village Community Economic Empowerment in Pidie Regency: Challenges and Opportunities in Utilizing Information Technology and Enhancing Participation - AG, Munzir; Larasati, Endang; Warsono, Hardi; Kismartini, Kismartini (Journal Public Policy, 2024)
Economic empowerment of rural communities is a global issue which has once again become an important program implemented in Indonesia, especially in the village fund program. There are many obstacles faced by villages, including villages in Pidie Regency, Aceh Province, in its implementation. This research explores the factors that influence the supporting and inhibiting factors for the economic empowerment of village communities in Pidie Regency. This research uses a qualitative method with a descriptive approach, which aims to understand the phenomena experienced by research subjects, such as behavior, perceptions, motivations, actions, completely and explicitly, using a natural approach in a natural context. The research results show that the supporting factors for information access are the use of information and communication technology and freedom of information. On the other hand, the inhibiting factor is that information from the community and the information media available in the village still need to be increased. Supporting factors for participation are the opportunities to participate provided by the government. Meanwhile, the inhibiting factors are the low ability and desire or willingness to participate in society as well as the need for more awareness from village communities regarding village community economic empowerment activities. The limitation of this research is that it only uses two factors to look at the factors that influence the economic development of village communities, so it is hoped that there will be other research that uses several other influencing factors. The village government in Pidie Regency is expected to pay attention to these influencing factors in carrying out economic empowerment of village communities.